Reconstruction of Islamic Family Law Based on Qawāʿid Maqāṣidiyyah: Strengthening Gender Justice and Child Protection in the Modern Legal System - Nurhilal Nazri Arif; Rahman Alwi (JURNAL MAHASISWA YUSTISI, 2026)
The reform of Islamic family law faces significant challenges in achieving gender justice and child protection, particularly in issues of divorce, child custody (ḥaḍānah), and wives’ rights. The predominance of normative fiqh approaches often fails to adequately respond to contemporary social dynamics and the demand for substantive justice within modern legal systems. This article aims to reconstruct Islamic family law by positioning qawāʿid maqāṣidiyyah as a methodological framework for legal reform. This study employs normative legal research with conceptual and philosophical approaches, examining the principles of maqāṣid al-sharī‘ah, especially justice (al-‘adl) and public interest (maṣlaḥah), and their relevance to gender justice and child protection. The findings indicate that the application of qawāʿid maqāṣidiyyah such as al-ḍarar yuzāl, ḥifẓ al-nasl, and taṣarruf al-imām manūṭun bi al-maṣlaḥah provides a robust foundation for reconstructing Islamic family law in a more responsive, contextual, and child-centered manner. This article argues that the reform of Islamic family law should move beyond purely normative reinterpretation toward a systematic maqāṣid-based approach to ensure the protection of women’s and children’s rights within modern family law systems.